2019
DOI: 10.1055/s-0039-1700840
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Opioid Consumption and Length of Stay Using an IPACK and Adductor Canal Nerve Block following Total Knee Arthroplasty

Abstract: Peripheral nerve blocks such as a femoral + sciatic block have demonstrated significant pain relief following TKA. However, these nerve blocks have residual motor deficits which prevent immediate postoperative ambulation. The purpose of this study was to compare outcomes in patients undergoing primary TKA with femoral and sciatic (Fem + Sci) motor nerve blocks versus an adductor canal and the interspace between the popliteal artery and the capsule of the posterior knee and adductor canal block (IPACK + ACB) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
(28 reference statements)
1
31
0
Order By: Relevance
“…Furthermore, opioid requirements, length of stay, and distance walked on postoperative day 0 were all analyzed in a review of 100 TKA patients who received IPACK + ACB compared to femoral nerve block and SNB. It was concluded that the IPACK + ACB combination resulted in earlier ambulation, decreased opioid use, and decreased length of stay [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, opioid requirements, length of stay, and distance walked on postoperative day 0 were all analyzed in a review of 100 TKA patients who received IPACK + ACB compared to femoral nerve block and SNB. It was concluded that the IPACK + ACB combination resulted in earlier ambulation, decreased opioid use, and decreased length of stay [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors acknowledge that confounders within the studies included in this review must be taken into account, such as flaws in study design or execution of other treatments that may provide for posterior knee coverage such as sciatic blocks or PAI in some of the experimental arms. 13 , 40 When assessing only RCTs with treatment arms comparing iPACK+ACB vs PAI+ACB, two RCTs 29 , 31 reported no clinically significant difference in opioid consumption or pain scores with movement. While this may indicate that PAI targets similar nerves that overlap with the iPACK coverage, additional objective studies, such as cadaver studies comparing injectate spread, are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Eccles CJ et al . [ 11 ] demonstrated that patients receiving IPACK block in combination with ACB could be ambulated early, had decreased opioid consumption and duration of hospitalisation when compared to femoral and sciatic nerve blockade. However, both these studies were retrospective in nature.…”
Section: Discussionmentioning
confidence: 99%